The Concept of Prajna in Buddhis’s Teaching Toward Crises of Identity in Globalization Era - Mohammad Djaya Aji Bima Sakti; Yusuf Muhtadi (Jounal Nyanadassana, 2025)
This article aims to explain the nature of Prajna as one of the various teaching in Buddhism. As the main concept, Prajna teach the fundamental aspect for mindfulness steps, that the nature of man is to wise for reality. This teaching of Prajna become one of the variant of doctrine toward the Globalization era. Meanwhile this era produced many problem of life, such as identity crises, moral degradation and the weakening of spirituality. This study aims to examine the essence of Prajna in Buddhist teachings and its relevance in addressing the challenges of globalization, especially toward Crises of Identity. This article used a library research by using the phenomenological approaches. The findings reveal that Prajna is relevant in guiding modern humans to act wisely in the use of technology, to be critical of global popular culture, and to show concern for the environment.